In What Circumstances Flexible Working Arrangement Possible to be Implemented?: A Literature Review - Fatmawati Aditya Febrita; Eko Prasojo (Pelopor Publikasi Akademika, 2023)
A new paradigm has emerged in the world of work amidst the widespread of the COVID-19 pandemic. One concept that has garnered attention is the